Analisis Aplikasi Temperature Control and Monitoring System Pada Akuarium Pendederan Ikan Gurame Berbasis Android - Ika Indah Lestari; Muh. Akbar Setiawan; Singgih S. A. (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2020)
This research aims to analyze the Application of Temperature Control and Monitoring System in the Android-based Gouramy Hatching Aquarium. This application was developed with the concept of the Internet of Things (IoT) to integrate data and connect all electronic devices to the internet network. While the webserver that we used is blynk.io. This application is evaluated on the aspects of product testing and benefit testing. Product testing is based on The Dimension of Quality for Goods which consists of Operation, Reliability and Durability, Conformance, Serviceability, Appearance, and Quality. The product test results obtained from the 6 attributes were 82.26%. This means that the products produced are of good quality. The benefits test covers the aspects of Useability, Learnability, Efficiency, and Acceptability. The results of the benefits test were obtained at 90.98% with the highest score in the Useability and Efficiency aspects of 98.75%. This shows that this application is useful for users, especially in terms of useability and efficiency.